Monthly Mean Hourly Diffuse Solar Radiation for Lesotho - Gopinathan, K K (Annals of Arid Zone, 2016)
The applicability of Liu and Jordan's mtethod to calculate the hourly diffuse solar radiation was tested for two locations in South Africa by comprison with the available measured data. The excellent agreclI'ent betwcen measured and estimated values suggested the suitabiiity of Liu and Jordan model to the Southern African region. The calculated hourly diffuse radiation data can serve as a useful reference for radial ion applications.